Changing the Rules. Inclusive Language - Discacciati, Vilda R. (Revista del Hospital Italiano de Buenos Aires, 2023)
Inclusive language reaches academic writing in a dissemination text and prompts us to review the current, standardized, dominant norm. To accept the authors’ way of expression is an opportunity to make changes that allow us to accompany social changes from the academic text.